Analisis Pola Distribusi Pemasaran Usaha Ikan Air Tawar Didesa Perian Kecamatan Montong Gading - Susilawati Susilawati; Rohaeniyah Zain (Universitas Hamzanwadi, 2023)
This study aims to find out how the distribution pattern of freshwater fish marketing in Perian Village, Montong Gading sub-district, because the majority of people in Perian Village as freshwater fish farmers make the marketing pattern of freshwater fish in Perian Village need to be investigated. This study uses a descriptive type of research with a qualitative approach. The data collection technique used was an unstructured interview technique with the Perian village head, community leaders, collectors and freshwater fish farmers, then continued by using observation and documentation techniques. The results of this study indicate that the marketing distribution pattern of freshwater fish business in Perian Village there are three marketing patterns, namely channel 1, namely producers selling fish to final consumers directly, marketing channel 2, namely producers selling fish to collectors and collectors distributing them to retailers and retailers selling fish. to final consumers and marketing channel 3, namely producers selling fish to collectors and collectors selling to TPI (Fish Fishing Places) and to restaurants or lesehans then reaching the final consumer. The economic impact caused by freshwater fish business is that the majority of the people in Perian Village who are in the freshwater fish business can be helped in meeting family needs compared to before trying freshwater fish.